Improving evidence based practice in postgraduate nursing programs: A systematic review: Bridging the evidence practice gap (BRIDGE project). (April 2018) - Hickman, Louise D.; DiGiacomo, Michelle; Phillips, Jane; Rao, Angela; Newton, Phillip J.; Jackson, Debra; Ferguson, Caleb
Abstract: Background: The nursing profession has a significant evidence to practice gap in an increasingly complex and dynamic health care environment. Objective(s): To evaluate effectiveness of teaching and learning strategies related to a capstone project within a Masters of Nursing program that encourage the development of evidence based practice capabilities. Design: Systematic review that conforms to the PRISMA statement. Sample: Master's Nursing programs that include elements of a capstone project within a university setting. Data Sources/Review Methods: MEDLINE, CINAHL, Cochrane Database of Systematic Reviews, ERIC and PsycInfo were used to search for RCT's or quasi experimental studies conducted between 1979 and 9 June 2017, published in a peer reviewed journal in English. Results: Of 1592 studies, no RCT's specifically addressed the development of evidence based practice capabilities within the university teaching environment. Five quasi-experimental studies integrated blended learning, guided design processes, small group work, role play and structured debate into Masters of Nursing research courses. All five studies demonstrated some improvements in evidence based practice skills and/or research knowledge translation, with three out of five studies demonstrating significant improvements. Conclusions: There is a paucity of empirical evidence supporting the best strategies to use in developing evidence based practice skills and/or research knowledge translation skills for Master's Nursing students. As a profession, nursing requires methodologically robust studies that are discipline specific to identify the best approaches for developing evidence-based practice skills and/or research knowledge translation skills within the university teaching environment. Provision of these strategies will enable the nursing profession to integrate the best empirical evidence into nursing practice. Highlights: Integration of blended learning, guided design process, small group work, role play and structure debate into courses demonstrated some improvements in evidence-based practice skills and research knowledge translation. Strategies that encourage a supportive professional learning environment and promotion of research culture will facilitate knowledge translation. Collaboration with research familiar personnel as a component of the Masters Capstone project is likely to foster evidence-based practice integration. Guided approaches progression through levels of difficulty and critical thinking are ideal for the development of confidence among students in evidence-based practice.